Factors affecting the genetic diversity of Lotus corniculatus in the Hemi-boreal zone of Baltic States and their agronomical implications - Sultan, Yaqoob; Ullah, Izhar; Paľove-Balang, Peter; Mukhtiar, Asif; Mudasir, Muhammad; Bačovčinová, Michaela; Kemešyte, Vilma; Liatukiene, Aurelija; Petrauskas, Giedrius; Norkevičienė, Eglė (Frontiers in Plant Science, 2026)
Bird’s-foot trefoil (BFT) is an underutilized perennial legume of increasing importance for sustainable agriculture in Europe, particularly within the Hemi-boreal zone of the Baltic states. It is a resistant, symbiosis-forming, and abiotic stress resistance making it a nitrogen-fixing soil, high potential of biodiversity conservation, pasture restoration, and low input farming systems. Yet, molecular genetic investigations of BFT with systematic investigations populations, of Lithuania, of Latvia, and of Estonia, are practically non-existent, to develop a critical knowledge gap in the agricultural development of the region and conservation planning. This gap is filled by this review through (1) synthesizing global evidence on BFT genetic diversity, population structure, adaptive traits, and characteristics revealed by molecular markers; (2) surveying the little information on the same already available distribution, habitat diversity, and ecotypic variation of the Baltic region; (3) the critical assessment of the applicability of the findings of neighboring European, Transcaucasian, and Central Asian races to Baltic Hemi-boreal states; and (4) setting out a research framework and future research priorities in Baltics-specific genetic studies. We point out the action of ecological gradients, climatic anthropogenic activities, pressures, and biotic interactions on population differentiation and adaptability based on research of the neighboring lands and ecological zones. By directly filling in the existing gap of lack of Baltic-specific molecular data, our analysis creates a level of cognition, which is a synthesis of global comprehension research and a knowledge road map of addressing gaps of knowledge that are critical. The findings underscore that BFT needs genetic diversity to be able to persist despite alteration. Hemi-boreal status and satisfaction of European Union biodiversity and agriculture sustainability goals. Local genetic resources will be tapped through the collection of customized germplasm, which will be molecularly characterized and bred according to their specific ecotype. This approach is essential for developing robust forage systems and supporting productive grassland restoration in the Baltic States. The findings underscore that genetic diversity in BFT is essential for its persistence under changing Hemi-boreal conditions and for meeting European Union biodiversity and agriculture sustainability goals. High genetic diversity provides the adaptive foundation necessary for breeding stress-tolerant cultivars, enhancing nitrogen fixation efficiency, and maintaining ecosystem resilience under climate variability and evolving agricultural practices. The conservation of local genetic resources, molecular characterization, and breeding of ecotypes will be crucial for utilizing these resources to develop resilient forage systems and promote efficient grassland recovery in the Baltic States, where baseline genetic diversity data remains limited.